Implementation of Internet of Things (IoT) in Smart Medicine Box for the Elderly : Implementasi Internet of Things (IOT) pada Kotak Obat Pintar untuk Lansia - Susanto, Yeremia Yudha Setia Graha; Restyandito; Saputra, Laurentius Kuncoro Probo (JOINCS (Journal of Informatics, Network, and Computer Science), 2023)
Consuming medicine on time is important for people who are sick. Medicine that prescribed by a doctor or pharmacist have various kind of rules, for example some medicine must be taken 3 times a day, 2 times a day, and 1 time a day, then there are rules after eating or before eating. Patients treated in the hospital are supervised by nurses, doctors, and receive more supervision from the hospital, but what if the patient is outpatient and the patient is an elderly person. With the presence of IoT technology that is not too expensive, a smart medicine box was made to be used to remind outpatients to take medicine which implements IoT technology and the android application used to manage the pillbox. The medicine box can remind patients to take medicine with the alarm module that is in the smart medicine box. System Usability Scale (SUS) is used to measure the success of the application. Smart medicine box is tested directly with data created to test the existing system. The result of testing the smart medicine box with existing data show that for each existing case, the smart medicine box system runs as it should. Application test results from all respondents received an average score of SUS 73,75. The score results show that the application can be accepted, get a grade scale worth B, and get good grades.